Electrolytes for Lithium‐Ion Batteries: Chemical Changes over Time and in the Presence of Impurities - Ulf Breddemann; Krum Banov; Miriam Khodeir; Petr Novák (ChemElectroChem)
In this study, the impact of typical contaminants—metal carbonates, metal sulfates, and metal acetates with M = Li, Ni, Mn, and Co—on the degradation of the commercial LP30 electrolyte is systematically investigated. Using a combination of electrochemical methods, inductively coupled plasma optical emission spectroscopy, nuclear magnetic resonance spectroscopy, and thermodynamic analyses, the solubility of these impurities, their influence on electrolyte decomposition, and their effect on NMC 811‐based positive electrodes are assessed. Our results indicate that the presence of transition metal contaminants accelerates electrolyte aging, leading to the formation of decomposition products such as HF, OPF2(OH), and OPF(OCH3)2). Electrochemical impedance spectroscopy and galvanostatic cycling reveal that these impurities contribute to increased charge transfer resistance and capacity fading. Notably, nickel‐based contaminants exhibit the strongest impact, likely due to their catalytic activity in side reactions. A detailed thermodynamic analysis further elucidates the reaction pathways responsible for the formation of these degradation products. This study highlights the complex interplay between electrolyte contamination, aging processes, and electrochemical performance, providing valuable insights into the stability of lithium‐ion battery electrolytes and the necessity of impurity control in battery recycling and material purification.